As ações afirmativas como tensão à estrutura universitária: o caso da UEL (2004-2018) - Silva, Nikolas Gustavo Pallisser (2019)
The multiple racial inequalities, components of the everyday life of the Brazilian Negro, were historically questioned in different ways, mainly by the actions of the Black Movement. Claimed by the latter, racial quotas initially thought of as a form of inclusion of young blacks, present as a corollary the questioning of a university structure that sought to make the presence and history of these subjects invisible, as beings not endowed with rationality, inventive and creative capacity. , as beings little endowed with humanity. Having this problem of research, by object, the policy of affirmative action adopted by the State University of Londrina (UEL) to the present (2004-2018), its general objective was to understand the possible transformations occurred in the university structure with the adoption of vacancies for certain student profiles. The specific objectives are: a) to verify which changes regarding the faculty occurred, if they occurred; b) to investigate which changes have been reached - the academic daily life of the student body; and c) to know the performance of the main managers who participated and participate in university administration. To undertake this study, we used the qualitative methodology, as well as documentary research and interviews (with students, teachers and managers). The theoretical bases of this research have, among other references, the contributions of the research already done on affirmative action policies in Brazil and the Sociology of Race Relations. Besides these, the Cultural and Post-Colonial Studies that helped us to understand aspects underlying the policy of affirmative actions, such as coexistence in difference, the construction of other frames of reference on the black subject and the processes of recognition. Thus, we conclude that the vacancies reserved by racial criteria exert a tension on this structure, insofar as the meaning of being shareholder is questioned by the subjects themselves and undergoes changes. The inclusion of black students from public schools already demonstrates the alteration of the aesthetic universe of these courses. Moreover, the reaction to cases of racism and the research interests of quota students alter the student profile and, with this, bring new questions and new pedagogical and theoretical challenges to the university structure itself.